Labor-dependent capital income taxation that encourages work and saving - Sagiri Kitao (Federal Reserve Bank of New York, 2010)
This paper proposes a simple mechanism of capital taxation that is negatively correlated with labor supply. Using a life-cycle model of heterogeneous agents, I show that this tax scheme provides a strong work incentive when households possess large assets and high productivity later in the life cycle, when they would otherwise work less. This reformed system also adds to the saving motive and raises aggregate capital. Moreover, the increased economic activities expand the tax base, and the revenue-neutral reform results in a lower average tax rate. My findings show that this tax scheme improves long-run welfare and that the majority of current generations would experience a welfare gain from a transition to the reformed system.
Keywords: E62; H24; H31; 330; Capital income taxation; life cycle